Persepsi Guru dalam Implementasi Kurikulum Merdeka di SMA Negeri 1 Sukoharjo (Analisis Teori Fenomenologi Persepsi Maurice Merleau-Ponty) - Lia Nur Halimah; Nurhadi Nurhadi; Ghufronudin Ghufronudin (Journal on Education, 2023)
The Ministry of Education, Culture, Research and Technology of the Republic of Indonesia often changes policies regarding the applicable curriculum, and currently schools in Indonesia are in the process of transitioning to using the Merdeka Curriculum. SMA Negeri 1 Sukoharjo, which is the barometer for schools in Sukoharjo, also implements the Merdeka Curriculum according to applicable regulations and is further strengthened by the mandate of the Education Office. This study aims to determine teachers' perceptions regarding the implementation of the Merdeka Curriculum at SMA Negeri 1 Sukoharjo. Informants in this study are driving teachers and non-moving teachers who are implementing the Merdeka Curriculum. This study uses content analysis techniques to find out about teacher perceptions in terms of Maurice Merleau-Ponty's phenomenological theory of perception. This study concludes that teacher perceptions are strongly influenced by teaching experience, intentionality in education, and a teacher's idealism.